2016
DOI: 10.2174/1874325001610010500
|View full text |Cite
|
Sign up to set email alerts
|

Microgeodic Disease Affecting the Fingers and Toes in Childhood: A Case Report

Abstract: Microgeodic disease is a disease of unknown etiology that affects the fingers and toes of children, with ≥ 90% of cases involving the fingers alone. We present a rare case of microgeodic disease affecting an index finger and two toes simultaneously in a 7-year-old girl. X-ray and magnetic resonance imaging (MRI) showed multiple small areas of osteolysis in the middle phalanges of the left index finger, hallux, and second toe. Microgeodic disease was diagnosed from X-ray and MRI findings, and conservative thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…2,5 However, rare complications including pathological fracture and subsequent malunion have been reported. 3,6 In summary, the present case demonstrated that microgeodic disease can occur even in older individuals. When chilblain-like symptoms persist, microgeodic disease should be considered in a differential diagnosis to prevent complications and unnecessary treatment.…”
supporting
confidence: 55%
See 2 more Smart Citations
“…2,5 However, rare complications including pathological fracture and subsequent malunion have been reported. 3,6 In summary, the present case demonstrated that microgeodic disease can occur even in older individuals. When chilblain-like symptoms persist, microgeodic disease should be considered in a differential diagnosis to prevent complications and unnecessary treatment.…”
supporting
confidence: 55%
“…The details of this survey are given in a previous study. 6 The present study was approved by the Research Ethics Committee of the National Center for Geriatrics and Gerontology (No, 1534). Attitudes toward PWD's social participation were measured using two questions:…”
Section: Author Contributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment for microgeodic disease is largely supportive, aimed at keeping the patient warm and dry 1 13. As in our case, this involves avoiding exposure to the cold by wearing layered clothing and keeping peripheries covered.…”
Section: Discussionmentioning
confidence: 97%
“…Similarly, treatment with antibiotics, anti-inflammatories and other unnecessary pharmacotherapies can be avoided with appropriate diagnosis. Once recognised, the majority of cases will heal spontaneously without residual deformity, however, rare complications include pathological fracture and subsequent malunion 11 13 14…”
Section: Discussionmentioning
confidence: 99%